Role of oral erythromycin for feed intolerance in neonates - A randomized controlled trial - Shekharappa, Chandrakala Bada; Bhat, Swarnarekha; Chandrasekaran, Ashok (Indian Journal of Child Health, 2018)
Objective: The objective of this study was to compare the effect of high and low dose of erythromycin with placebo and to determine the efficacy and safety of oral erythromycin for feed intolerance in neonates admitted to the neonatal intensive care unit. Methodology: The study was a double-blind, randomized, and placebo-controlled trial. Term and preterm babies having feed intolerance were included in the study, and babies with congenital malformations, necrotizing enterocolitis, and sepsis were excluded from the study. After parental consent, the subjects were randomized into Groups 1, 2, or 3 to receive low-dose (3 mg/kg/dose) or high-dose (10 mg/kg/dose) oral erythromycin estolate or the placebo (equal volume of 5% dextrose). Feeding of all the study neonates was managed as per the unit protocol and babies were monitored for the complications. The primary outcome was the time to reach full feeds of 150 ml/kg/day, without significant gastric residuals. Results: Of 58 eligible babies, 84.5% were preterm babies. The median time for reaching full feeds with placebo was 6 days with interquartile range 3